2019
DOI: 10.3389/fpsyg.2019.00598
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Parental Attachment and Mobile Phone Dependence Among Chinese Rural Adolescents: The Role of Alexithymia and Mindfulness

Abstract: Mobile phone has experienced a significant increase in popularity among adolescents in recent years. Findings indicate dependence on mobile phone is related to poor parent-child relationship. However, previous research on mobile phone dependence (MPD) is scant and mainly focus on adult samples. In this view, the present study investigated the association between parental attachment and MPD as well as its influence mechanism, in sample of adolescents in rural China. Data were collected from three middle schools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 87 publications
(97 reference statements)
1
19
0
Order By: Relevance
“…In a study on adolescents from middle schools in rural China, parental attachment negatively predicted mobile phone addiction [51]. This effect was partially mediated by depression.…”
Section: Female Gendermentioning
confidence: 96%
“…In a study on adolescents from middle schools in rural China, parental attachment negatively predicted mobile phone addiction [51]. This effect was partially mediated by depression.…”
Section: Female Gendermentioning
confidence: 96%
“…In addition, it had been found that if we enhance an individual's level of awareness, the mindfulness displays a protective role for problematic habitual behaviors such as disordered mobile phone use (Lan et al, 2018). Li and Hao (2019) have reported the moderation effect of mindfulness in the positive relationship between alexithymia and problematic mobile phone use where the adverse impact was weakened under the condition of high level of mindfulness. However, there is no study to our knowledge that has examined the specific roles of the mindfulness facets in this relationship.…”
Section: Mindfulnessmentioning
confidence: 99%
“…Therefore, the feeling of not being accepted and the lack of a sense of belonging might lead alexithymic subjects to use alternative modalities to communicate and interact with others (e.g. online platforms, Internet, and mobile phones) which may result in the early development of a technological addiction (46). Overall, one could argue that alexithymia might be both a stable personality trait that may constitute a vulnerability/risk factor for the development and/or maintenance of an addiction disorder, and a defensive mechanism (i.e., a variable state) secondary to a psychological distress which may arise or worsen an SUD/AUD or a behavioural addiction already present (3,53).…”
Section: Discussionmentioning
confidence: 99%
“…Mobile phone addiction is a behaviour characterized by an excessive indulgence to activities related to mobile phones, accompanied by a constant dependence on mobile phones, which results in a general loss of self-control and compromised psychological and social functioning (44)(45)(46). Mobile phone addicts might possess emotional recognition deficits, which may lead to more interpersonal issues as they usually attempt to cover/mask their own emotional states by escaping from reality by means of mobile phones (9).…”
Section: Mobile Phone Addiction and Alexithymiamentioning
confidence: 99%